Sumber Daya Manusia Usaha Kecil dan Menengah dan Perilaku Inovasi: Tinjauan Literatur Sistematis - Eni Sulistyawati (SMARTINDO, 2023)
This study aims to get an overview of existing studies on innovation behavior (PI) in human resources (HR) for small and medium enterprises(SMEs). This research was conducted using a systematic literature review (TLS) of 255 research articles, which were then filtered for titles andabstracts so that they became 65 research articles, and finally filtered all contents so that they became 16 research article s. This systematicliterature review (TLS) in the period from 2016 to 2022 was followed up with an analysis of the trends and background of SMEs in conductingbusiness innovation. The research results obtained based on the AMO method, the practice of SME HR in increasing motivation to innovate,namely increasing ability, there is motivation for innovation.The five factors that influence SME and PI human resources in this study are increased knowledge capacity, mastery of technology, marketorientation, opportunity openness, and leadership motivation.The results of this study can provide practical information for MSE HR for the development of MSE HR systems that produce inn ovativebehavior so that it can help improve the company's innovation and development capabilities.Therefore, this research is expected to be a reference for further research by specifically photographing the role of PI individually so that thelevel of effectiveness of each SME HR can be seen in their work effectiveness.